Danshen-Honghua Ameliorates Stress-Induced Menopausal Depression in Rats - Gu, Simeng (Neural plasticity, 2018)
Objective: Previously, we have shown that Danshen-Honghua (DSHH) for cognitive deficits after ischemia induced impairments of the hippocampus. Here, we investigate the effects of DSHH on stress-induced depression in menopausal rats